A Search for Freshwater in the Saline Aquifer of Coastal Bangladesh. Issue 4 (11th September 2019) - Peters, Chelsea N.; Hornberger, George M.
Abstract: In the polder region of coastal Bangladesh, shallow groundwater is primarily brackish with unpredictable occurrence of freshwater pockets. Delta building processes, including the codeposition of fresh‐to‐saline porewater and sediments, have formed the shallow aquifer. Impermeable clay facies and the lack of a topographical gradient limit the flow of groundwater and its mixing with surface water so controls on spatial variability of salinity are not obvious. By characterizing groundwater‐surface water (GW‐SW) interactions, this study attempted to identify areas of potable groundwater for the polder communities. We used transects of piezometers, cores, electromagnetic induction, and water chemistry surveys to explore two sources of potential fresh groundwater: (1) tidal channel‐aquifer exchange and (2) meteoric recharge. Fresh groundwater proved difficult to find due to heterogeneous subsurface lithology, asymmetrical tidal dynamics, extreme seasonal fluctuations in rainfall, and limited field data. Geophysical observations suggest substantial lateral variability in shallow subsurface conductivity profiles. Piezometers show varying degrees of tidal pressure attenuation away from the channels. Nevertheless, the active exchange of freshwater appears to be limited due to low permeability of banks and surface sediments. Results indicate that pockets of fresh groundwater cannot be identified using readily available hydrogeological methods, so alternative drinking water sources should be pursued. By better understanding the hydrogeology of the system, however, communities will be better equipped to redirect water management resources to more feasible and sustainable drinking water options. Abstract : Article impact statement : Potable groundwater resources are inadequate in coastal Bangladesh due to limited tidal channel‐aquifer exchange and meteoric recharge.